Carl Schmitt and the Politics of Hostility, Violence and Terror - Slomp, G. author. aut Link
VIII, 182 p.
Keywords: Carl Schmitt's friend/enemy principle is exposed to in-depth philosophical analysis and historical examination with the aim of showing that the political follows hostility, violence and terror as form follows matter. The book argues that the partisan is an umbrella concept that includes the national and global terrorist.